2018
DOI: 10.2217/ijh-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

Chart Review Across EU5 in MM Post-ASCT Patients

Abstract: Aim:To understand the current treatment patterns, clinical outcomes and healthcare resource utilization–associated costs for multiple myeloma patients, post autologous stem cell transplant (ASCT) across Europe.Patients & methods:Medical records were used to abstract data for 337 multiple myeloma patients who had received ASCT.Results:Following ASCT, 7% received maintenance therapy prior to progression. Lenalidomide was the most frequently prescribed maintenance, second- and third-line therapy. Monthly resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
1
8
2
Order By: Relevance
“…Overall, changes in MM drug prescription patterns were associated with a trend toward reduced total cost of MM treatment. A European study found that hospitalization costs for patients receiving lenalidomide maintenance therapy were lower than for patients not receiving any maintenance therapy 18 , which aligns with our exploratory finding of reduced hospitalization costs following the approval of lenalidomide in 2010; however, further investigations are needed to quantify the impact of lenalidomide maintenance therapy on hospitalization costs in Japan. A noteworthy difference was observed in the changes in costs over time for patients above and below the age threshold of 65 years.…”
Section: Discussionsupporting
confidence: 82%
“…Overall, changes in MM drug prescription patterns were associated with a trend toward reduced total cost of MM treatment. A European study found that hospitalization costs for patients receiving lenalidomide maintenance therapy were lower than for patients not receiving any maintenance therapy 18 , which aligns with our exploratory finding of reduced hospitalization costs following the approval of lenalidomide in 2010; however, further investigations are needed to quantify the impact of lenalidomide maintenance therapy on hospitalization costs in Japan. A noteworthy difference was observed in the changes in costs over time for patients above and below the age threshold of 65 years.…”
Section: Discussionsupporting
confidence: 82%
“…A real-world analysis of medical records from five European countries (France, Germany, Italy, Spain and the UK) showed that patients receiving lenalidomide maintenance therapy had longer time to disease progression (39 vs 30 months) and considerably lower mean PPPM costs compared with patients who did not (EUR 638 vs EUR 1001), reflecting lower costs for hospitalizations, healthcare professional visits and monitoring tests, although costs for supportive drugs and other treatments were higher in those receiving maintenance therapy [32]. Notably, this study also showed that 7% of patients with MM received maintenance therapy after ASCT, and, of those, 88% received lenalidomide monotherapy as maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…The EORTC QLQ‐C30 was administered at screening (study days –15 to –1 prior to initiation of protocol therapy), the start of every cycle, end of treatment, every 4 weeks until start of next line of therapy after progression and twice thereafter. The EORTC QLQ‐MY20 was administered at screening, the start of every 3 cycles between cycles 1 and 25, end of treatment, every 4 weeks until start of next line of therapy after progression and twice thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…3 In clinical practice, the most commonly administered post-ASCT MT is the immunomodulator lenalidomide, which is the only agent approved for this use, followed by the proteasome inhibitor bortezomib (used off label in this setting). [4][5][6] Lenalidomide is associated with adverse events (AEs) including cytopenia, secondary malignancy, and dermatologic and gastrointestinal toxicities, 5 whereas bortezomib is associated with peripheral neuropathy. Discontinuations related to toxicity or patient-convenience issues are common with these treatments in routine care, occurring in 17%-29% of patients treated with lenalidomide and 7%-20% of patients treated with bortezomib.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation